O sincretismo de sistemas nas primeiras páginas da Folha de São Paulo e Agora São Paulo - Santos, Edson Alves dos (2007)
This work seeks to comphreend how is the construction of the meaning of the sense in the test of newspaper by th relation between the verbal and the visual systems understood as the expression`s syncretism. Investigate, in this researsh object, how the diferent kinds of syncretism have a function in the enunciactive and argumentatives estrategics taken over by an enunciator to drive yours enunciaters to determinated manner of being in the word; how your the use of different systems articulated is a way of promoting an acting over the other. To test this hypothesis, the work was divided in three stages. The first stage attends to a contextualization of the history of the Grupo Folha the addresser and his insertion among the others impress medias, settling the problem of the reseach and the object of its application the first page of the newsapaper: Folha de São Paulo e Agora São Paulo. The second stage turns to development of the analysis of the chosen corpus intent to describe and comprehend, by the generative path the plane of the contents, a textual composition as a syncretic manifestation. The third, and the last stage, concerns to the conclusion of the syncretism as a concretizer of the enunciatives mechanism that characterize distinctivily each journal. The Semiotic of Algirdas Julien Greimas is the theorical and methodological support of this reseach about the correlation of syncretism of expression and the enuntiation. In the Semiotic, the investigation of the structural syncretism in the media is an emergenting theme/ and the first steps, in this direction, have been given by the analysis of mediactic texts of Jean-Marie Floch. This resarch inserts itself in the core of these investigations about the mechanisms of syncretization, of intention behind of its use by medias and by the living in society, what increase the importance of its investigation for a socio-semiotic. The syncretism, conclude, is a way of adjusting of the newspaper to a public segmentation and the articulation of the two systems is a identitary qualifier of the newspaper and the place itself in respect to others that integrate the media. The expression syncretism is still used so as to the selection and the settling of the fomants of the expression promote only one enunciation that sustains the board of the syntactic positions between the actors of the discourse, thus as possibilite that fraction and interpretation of the facts have been taken as simulacres of true saying, producer of fiduciary contract between the newspaper and the reader